LAW JU'ALAH IN ISLAM - Ahmad Fadhly; Mhd. Yadi (Universitas Islam Negeri Ar-Raniry, 2023)
In everyday life humans cannot live alone or meet their own needs, in general humans certainly always do activities, in these daily activities there is work that cannot be done alone, so they must need others to do the work. Because of this, there must be a reward for the work done by the other person. In Islam, This wage or gift is called Ju'alah. To know how the law of ju'alah and the postulates related to jua'lah so that we can understand in taking istinbath laws related to ju'alah, these hadiths have a sanad that is tsiqah and fulfills the condition that the hadith can be accounted for even the eyes are not contradictory to the Qur'an, so that scientifically the hadith can really be believed that the hadith is true like the Prophet Muhammad SAW, so that based on the hadiths it is very clear that the law of ju'alah is permissible, even this transaction has existed since ancient times as explained in the Qur'an Surat Yusuf verse 72